Qualitative organizational research : best papers from the Davis Conference on Qualitative Research - Elsbach, Kimberly D. (Emerald Publishing Limited : IAP, 2005)
Over the past five years the Davis Conference on Qualitative Research has welcomed research projects by the very best qualitative, organizational researchers in the world. This conference has helped authors develop and hone theoretical ideas in an environment friendly to qualitative methods, and more importantly, has begun to build a community of qualitative researchers that work on organizational and management issues. The authors winning the "Best Presentation Awards" at the Davis Conference over the past five years have contributed chapters to this volume. The ideas in these chapters were "born" before the conference, but were nurtured through dialogue at the conference, and subsequently matured through later interactions among the community of qualitative scholars associated with the conference. As such, this volume represents the fruits of our collective labor as a qualitative research community. This collective and iterative process is a hallmark of qualitative methods, and often leads to a counter-intuitive, "ah-hah" experience for the researcher. This volume showcases some of the very best of those ah-hah experiences from the organizational, qualitative research community.
"The best presentation winners and runners-up from the past five years of the Davis Conference have versions of their presentations included in this volume."
Keywords: Organization -- Research -- Congresses.; Management -- Research -- Congresses.; Qualitative research -- Congresses.; Business & Economics -- Industrial Management.; Management and management techniques.; elektronické knihy; electronic books